Relationship between high-resolution computed tomography quantitative imaging analysis and physiological and clinical features in antisynthetase syndrome-related interstitial lung disease - Donald P Tashkin; Rohit Aggarwal; Chester V Oddis; Grace Kim; Fereidoun Abtin; Daniela Markovic; Christina Charles-Schoeman; Galina Marder; Jonathan Goldin; Paul F Dellaripa; Swamy Venuturupalli; Gary Matt Hunninghake; et al. (RMD Open)
Objectives To explore the association between the extent of CT abnormalities by quantitative imaging analysis (QIA) and clinical/physiological disease parameters in patients with antisynthetase syndrome associated interstitial lung disease (ARS-ILD).Methods We analysed 20 patients with antisynthetase antibodies and active ILD enrolled in the Abatacept in Myositis-Associated Interstitial Lung Disease study. High-resolution chest CT was obtained at weeks 0, 24 and 48 and QIA scored the extent of ground glass (quantitative score for ground glass), fibrosis (quantitative score for lung fibrosis, QLF) and total ILD (quantitative ILD, QILD). Mixed-effects models estimated longitudinal QIA scores over time. Associations between QIA scores with clinical/physiological parameters were analysed longitudinally using repeated-measures mixed-effects models.Results Patients were median age 57 years, 55% males and 85% white. Higher (worse) baseline QIA scores correlated with lower baseline forced vital capacity (FVC) and diffusing capacity adjusted for haemoglobin (DLCO). Longitudinal QIA trajectories trended towards improving scores during the trial, and patients on O2 at baseline had worsening QIA trajectories which were different from patients who were not on O2. Longitudinal QIA scores demonstrated strong associations with both FVC and DLCO over time. Higher QILD scores over time were also associated with worse dyspnoea scores, pulmonary visual analogue scale, physician and patient global disease activity, health status in 6/8 domains of the Short Form-36 and higher oxygen requirements. Patients with significant radiographic improvement at 48 weeks had higher baseline QLF, QILD and worse DLCO.Conclusions Longitudinal QIA scores associate with lung physiology, patient perception of respiratory status, overall disease activity and quality of life over time in ARS-ILD. QIA may allow reproducible monitoring of disease progression and response to therapy over time.Trial registration number NCT03215927.